2011
DOI: 10.1021/ja105975a
|View full text |Cite
|
Sign up to set email alerts
|

Face-to-Face Arene−Arene Binding Energies: Dominated by Dispersion but Predicted by Electrostatic and Dispersion/Polarizability Substituent Constants

Abstract: Parallel face-to-face arene-arene complexes between benzene and substituted benzenes have been investigated at the MP2(full)/6-311G** and M05-2X/6-311G** levels of theory. A reasonably good correlation was found between the binding energies and the ∑|σ(m)| values of the substituted aromatics. It is proposed that a substituent |σ(m)| value informs on both the aromatic substituent dispersion/polarizability and the effect the substituent has on the aromatic electrostatics. Supporting this hypothesis, a combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
166
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(185 citation statements)
references
References 66 publications
17
166
0
1
Order By: Relevance
“…[3,51,52] Recent work has suggested that dispersion and electrostatics are important contributing forces in aromatic stacking interactions. [38,53,54] Scheme 1. Reduction of 3-nitro-1,8-naphthalic anhydride and condensation reaction for formation of 3-substituted naphthalimides [39] Scheme 2.…”
Section: Initial Attempts At Correlating the δT M Valuesmentioning
confidence: 99%
See 2 more Smart Citations
“…[3,51,52] Recent work has suggested that dispersion and electrostatics are important contributing forces in aromatic stacking interactions. [38,53,54] Scheme 1. Reduction of 3-nitro-1,8-naphthalic anhydride and condensation reaction for formation of 3-substituted naphthalimides [39] Scheme 2.…”
Section: Initial Attempts At Correlating the δT M Valuesmentioning
confidence: 99%
“…In parallel face-to-face conformations of benzene-substituted benzene dimers, electrostatics and dispersion have been shown to contribute most significantly. [38,53,54,68,[73][74][75][76] The Π π parameter was developed from benzene-monosubstituted benzene dimers (Fig. 3) where the substituted benzene substituent corresponds to the naphthalimide substituents in intercalators 1b -3b, 4 -9, and 11.…”
Section: Initial Attempts At Correlating the δT M Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…The model combining dispersion and electrostatics may better reflect the nature of π-π interactions. Recently, several groups have identified substituent effects that can be correlated to the Hammett σ m parameters [15,32,36] . This ultimately led to the proposal of a local direct interaction model for π-π stacking [37,38] .…”
Section: Energy Decomposition Many Factors Contribute To Noncovalent mentioning
confidence: 99%
“…Intermolecular interactions minimize the energy of the complexes and play an important role in drug-receptor, protein-DNA, protein-protein interactions, etc., while intramolecular interactions minimize the energy of a molecule and are responsible for tertiary structure of proteins, DNA, RNA etc. [13][14][15][16]. In the literature, to facilitate arene interactions, several models have been proposed [17].…”
mentioning
confidence: 99%